60.0k views
5 votes
Ivan began to prove the law of sines using the diagram and equations below. sin(A) = h/b, so b sin(A) = h. sin(B) = h/a, so a sin(B) = h. Therefore, b sin(A) = a sin(B). Which equation is equivalent to the equation b sin(A) = a sin(B)? 

edit: the answer is b!

User Henrico
by
4.9k points

2 Answers

7 votes

(B.) sin(A)/a = sin(B)/b

Ivan began to prove the law of sines using the diagram and equations below. sin(A-example-1
User Anupam Basak
by
5.6k points
4 votes
the answer is b. its correct

User BeetDemGuise
by
4.7k points